Time-varying beta estimation in CAPM under the regime-switching Model - Roengchai Tansuchat (2018)
© 2018, Springer International Publishing AG. The objectives of this study are to analyze the risk of investment and to examine the structural change in the CAPM. To there ends, the Markov Switching dynamic regression is employed to construct the time varying beta risk when the market exhibits structural change. The model is applied to the Thai stock return data. The empirical results show a strong evidence of structural change in CAPM for four out of five Thai stocks of large market capitalization. We observe that the movement of Thai stocks fluctuated widely during the market turbulence, especially at the time of Thai financial crisis.